Statistical challenges of evaluating diversity patterns across environmental gradients in mega‐diverse communities. (May 2016) - Chao, Anne; Chiu, Chun‐Huo; Jost, Lou
Abstract: Ibanez et al. ( Journal of Vegetation Science, this issue) applied sample size‐ and coverage‐based rarefaction to analyse the elevational richness pattern in New Caledonian tree communities. We comment on the statistical assumptions behind rarefaction/extrapolation and suggest pooling small plot data to effectively assess/detect the diversity pattern. Broadening the analysis to include abundance‐sensitive diversity measures and phylogenetic information can provide important additional insights.